Efektivitas Gugatan Sederhana dalam Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama - Kiki Rofi'ah Alawiyah; Oyo Sunaryo Mukhlas; Ramdani Wahyu Sururie (STAI Al Musaddadiyah Garut, 2026)
The development of Islamic financial institutions in Indonesia has increased the potential for sharia economic disputes that require a settlement mechanism which is fast, simple, and low-cost. However, ordinary litigation procedures are often time-consuming and procedurally complex, making them less effective for small-value disputes. This study aims to analyze the procedural law governing the settlement of sharia economic disputes through the simple lawsuit mechanism in the Religious Courts and to assess its effectiveness in judicial practice. This research employs a normative juridical method using statutory and case study approaches. Data were collected through library research on primary and secondary legal materials and analyzed qualitatively. The results show that the simple lawsuit mechanism provides broader access to justice through a faster, simpler, and more affordable process conducted by a single judge with a maximum settlement period of 25 working days. This mechanism is effective for simple and small-value sharia economic disputes. However, its implementation still faces limitations when disputes involve third parties or complex sharia contracts, indicating that the mechanism has not been fully adaptive to all forms of sharia economic disputes. Keywords: Sharia economic law; procedural law; Religious Courts; simple lawsuit.